O olhar visto em voz alta: reflexões em torno de um certo realismo na ficção de Marcelino Freire - Cunha, Edson de Souza (2014)
This research aims at proposing an interpretative route of Marcelino Freire's writings, dealing with their connection with the reality as a reference field or a cultural reserve, from which are extracted the topics of such writings. Questioning the concepts of artistic realism and literary representation, we search alternatives on theories about the contemporary art to compose a repertoire that allow us to broaden the possibilities of interpretation of texts related to violence in three books from the author: Contos Negreiros, Angu de Sangue and Rasif – mar que arrebenta. Issues referring to the look and the gaze, as well as features related to the orality of such texts are privileged.